Design of Battery Charger System Using AC-DC Converters with Automatic Current Regulator - Rustam, Fathurrahman; Ponniran, Asmarashid (Evolution in Electrical and Electronic Engineering, 2023)
This paper focuses on the design of the power converter for a Lithium-Ion battery charger system. The use of batteries as a power source becomes in high demand that’s led to a good battery charger. For this purpose, a battery charger system using a power converter with a battery management system is proposed. This system implements the CC-CV charging method for controlling the voltage and current phase during charging. PI controllers are involved in obtaining constant current by the close loop system and microcontroller being programmed using Arduino Uno. This project result observed the output voltage and current and was analyzed. The features of this battery charger system have a protection mechanism cell balancing of the battery pack to ensure the safe and reliable operation of the Lithium-Ion battery pack. This charger is suitable for a wide range of lithium-ion batteries and can be used in applications such as electric vehicles, portable electronics, and renewable energy systems. Overall, this charger provides a reliable, efficient, and safe way to charge lithium-ion batteries using a power converter.